From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - McQuatters-Gollop, Abigail; Mitchell, Ian; Vina-Herbon, Cristina; Bedford, Jacob; Addison, Prue F. E.; Lynam, Christopher P.; Geetha, P. N.; Vermeulan, Estee Ann; Smit, Kaylee; Bayley, Daniel T. I.; Morris-Webb, Elisabeth; Niner, Holly J.; et al. (Frontiers in Marine Science, 2019)
Indicators are effective tools for summarising and communicating key aspects of ecosystem state and have a long record of use in marine pollution and fisheries management. The application of biodiversity indicators to assess the status of species, habitats, and functional diversity in marine conservation and policy, however, is still developing and multiple indicator roles and features are emerging. For example, some operational biodiversity indicators trigger management action when a threshold is reached, while others play an interpretive, or surveillance, role in informing management. Links between biodiversity indicators and the pressures affecting them are frequently unclear as links can be obscured by environmental change, data limitations, food web dynamics, or the cumulative effects of multiple pressures. In practice, the application of biodiversity indicators to meet marine conservation policy and management demands is developing rapidly in the management realm, with a lag before academic publication detailing indicator development. Making best use of biodiversity indicators depends on sharing and synthesising cutting-edge knowledge and experience. Using lessons learned from the application of biodiversity indicators in policy and management from around the globe, we define the concept of ‘biodiversity indicators’, explore barriers to their use and potential solutions, and outline strategies for their effective communication to decision-makers.